Pengaruh Pola Sebaran Sarana dan Prasarana Kesehatan Terhadap Aksesibilitas Pelayanan Kesehatan Masyarakat di Kabupaten Tegal Tahun 2016 - Aghnia Putri, Aprella Qonita; Puji, Hardati; Mochammad, Arifien (Geo-Image, 2018)
The location of health facilities and infrastructure should have a high degree of accessibility. The area of health care services will be greatly influenced by the level of accessibility. The location of facilities and health infrastructure that is easy to reach in terms of transportation, of course, has a special attraction for the community to visit it. This has resulted in the health service area exceeding the work area determined by the local government. Data analysis techniques used nearest neighbor analysis, accessibility index analysis and serviceability analysis. The results of this study indicate that 1) Distribution pattern of health center at sub-district level and doctors practice classified dispersed (dispered pattern), the pattern of distribution of the hospital classified unequally spread (random pattern) and pattern of distribution pharmacy in clustered. 2) The accessibility level in terms of distance to reach the location of health facility and infrastructure in Tegal Regency is mostly well classified / easy to reach. It's just that there are still some roads that still use paving, and in some districts are also still there are hollow road conditions. 3) The number of health facilities that have been fulfilled is the number of health center at sub-district level, and the hospital. The number of health facilities that have not been fulfilled is the number of community health sub-center, practice doctors and pharmacies.